Pengaruh Iman Terhadap Perkembangan Ilmu Pengetahuan dan Teknologi;Refleksi Kritis Iman Terhadap Revolusi Industri 4.0 - Hendra Paulinus Simbolon (Forum, 2022)
The purpose of this paper is to see the Role of Faith in the development of Science and Technology. This is because the development of science and technology has resulted in significant changes for society. This change is not only in the physical field, namely accelerating and helping humans to carry out tasks and support professionalism but also in the spiritual field where humans can think that they are everything. The methodology used in this paper is literature review. Where to do a critical reading of the sources obtained from library research. The results obtained from this paper indicate that there are fundamental changes caused by technological developments. The first development presents a revolution in human life where the revolution starts from revolution 1.0 - 4.0 at this time. This development also makes humans have different views about who they are and who their god is or in terms of religiosity. Finally, this change causes humans to question their faith. This is what causes the position of faith to affect humans.